Evaluation of clinical and laboratory markers of cardiometabolic risk in overweight and obese children and adolescents (Clinics, 2017)
OBJECTIVE: This study analyzed the frequency of cardiometabolic risk markers and metabolic syndrome occurrence in overweight and obese children and adolescents. METHODS: The participants included 161 overweight (n=65) and obese (n=96) individuals aged between 5 and 19 years. Clinical markers were assessed (body mass index, body fat percentage, waist circumference, acanthosis, systolic and diastolic blood pressures, laboratory parameters [glucose, insulin, cholesterol (total and fractions) and triglyceride levels and homeostasis model assessment of insulin resistance (HOMA-IR) index] and leptin and adiponectin levels). The frequency of changes, odds ratios and correlations among markers were determined. Metabolic syndrome was assessed according to International Diabetes Federation criteria. RESULTS: A high frequency of acanthosis (51.6%); increased waist circumference (45.4%), systolic blood pressure / diastolic blood pressure (8.1% / 9.3%), glucose (10%), insulin (36.9%) and HOMA-IR (44.3%) values; and reduced high-density lipoprotein levels (47.2%) were observed. Leptin levels were increased in 95% of obese and in 66% of overweight subjects. Adiponectin was decreased in 29.5% of obese and in 34% of overweight subjects. An odd ratio analysis revealed a greater probability of increased waist circumference (9.0), systolic blood pressure (4.1), triglyceride (2.3) and insulin (2.9) levels and HOMA-IR (3.0) in the obese group than in the overweight group. The clinical and laboratory parameters and leptin levels exhibited significant correlations, whereas adiponectin was negatively correlated with systolic blood pressure. The occurrence rate of metabolic syndrome was 13.6%. CONCLUSIONS: The high frequency of changes in clinical, laboratory and adipokine markers indicates the need for early interventions aimed at preventing cardiometabolic complications in adulthood.